EFFECTIVENESS OF IMPLEMENTING SANCTIONS BASED ON ARTICLE 38 OF LAW NUMBER 16 OF 2009 FOR TAXPAYERS - Putri Esta Napitu; Rony Andre Christian Naldo; Muldri P.J. Pasaribu (Jurnal Ilmiah Advokasi, 2024)
Taxes are an important source of revenue for the Government, collected from taxpayers. Income tax is one type of tax collected from taxpayers in the city of Pematang Siantar and Simalungun Regency. Therefore, it is expected that every taxpayer (WP) has legal awareness to fulfill their legal obligations such as filing tax returns. The legal fact is that every year there is a decreasing legal awareness among taxpayers, as they neglect their legal obligations. Given this legal fact, it is necessary to effectively enforce sanctions based on Article 38 of Law Number 16 of 2009. This research discusses the effectiveness of tax sanction enforcement. Accordingly, this research focuses on examining the effectiveness of applying sanctions based on Article 38 of Law Number 16 of 2009 for taxpayers in the city of Pematang Siantar and Simalungun Regency who fail to file tax returns. This research is prescriptive, using normative juridical methods, with using a statutory approach, and a conceptual approach. The type of data used is secondary data. The results of this research conclude that the enforcement of sanctions based on Article 38 of Law Number 16 of 2009 has not been effective yet. This ineffectiveness is related to the application of the ultimum remedium principle. Additionally, there are 6 (six) factors that can influence the effectiveness of applying sanctions based on Article 38 of Law Number 16 of 2009. Key Words: Effectiveness, Sanctions, Taxpayers